Pengaruh Net Profit Margin Dan Debt To Equity Ratio Terhadap Harga Saham Pada PT XL Axiata Tbk Periode 2014 - 2024 - Sari, Siti Ratna; Hermawan, Hengki (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of Net Profit Margin (NPM) and Debt to Equity Ratio (DER) on the share price of PT XL Axiata Tbk. The research method used is a quantitative method with secondary data in the form of company financial reports for the 2014–2024 period obtained from the official website of PT XL Axiata Tbk. The data were analyzed using SPSS version 25.0 through classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results show that, partially, NPM does not have a significant effect on stock prices, as indicated by a significance value of 0.245 > 0.05. Conversely, DER has a significant effect on stock prices with a significance value of 0.024 < 0.05. Simultaneously, NPM and DER were proven to have an effect on the stock price of PT XL Axiata Tbk, as indicated by the F test results with a significance value of 0.036 < 0.05. These findings confirm that the company's capital structure, particularly the DER ratio, plays an important role in influencing stock price movements, while the effect of NPM is more limited in part.